Raphael Semmes : the philosophical mariner - Spencer, Warren F., 1923- (University of Alabama Press, 1997)
Naval hero for all the South, Raphael Semmes (1809-1877) sailed two famous Confederate raiders. He outfitted CSS Sumter in 1861 and captured 18 Union merchant ships in six months before the raider was blockaded at Gibraltar. Next he took command of CSS Alabama, an English-built raider, and terrorized U.S. merchant vessels on the high seas from August 1862 until the raider was sunk in battle off Cherbourg in June 1864. During that two-year period, he captured more enemy merchant ships than any other cruiser captain in maritime history. He is considered one of the greatest ship's commanders that.